Oligomerization of adenosin-5'-O-ylmethylphosphonate, an isopolar AMP analogue: evaluation of the route to short oligoadenylates - Pressová, Martina; Budesínský, Milos; Kosiová, Ivana; Kopecký, Vladimír; Cvacka, Josef; Kasicka, Václav; Simák, Ondrej; Tocík, Zdenek; Rosenberg, Ivan (Biopolymers, 2010)
In an attempt to prepare a library of short oligoadenylate analogues featuring both the enzyme-stable internucleotide linkage and the 5'-O-methylphosphonate moiety and thus obtain a pool of potential RNase L agonists/antagonists, we studied the spontaneous polycondensation of the adenosin-5'-O-ylmethylphosphonic acid (p(c)A), an isopolar AMP analogue, and its imidazolide derivatives employing N,N'-dicyclohexylcarbodiimide under nonaqueous conditions and uranyl ions under aqueous conditions, respectively. The RP LC-MS analyses of the reaction mixtures per se, and those obtained after the periodate treatment, along with analyses and separations by capillary zone electrophoresis, allowed us to characterize major linear and cyclic oligoadenylates obtained. The structure of selected compounds was supported, after their isolation, by NMR spectroscopy. Ab initio calculation of the model structures simulating the AMP-imidazolide and p(c)A-imidazolide offered the explanation why the latter compound exerted, in contrast to AMP-imidazolide, a very low stability in aqueous solutions.
Keywords: Molecular Structure; Models, Molecular; Oligoribonucleotides; molekulární struktura; oxidace-redukce; Nuclear Magnetic Resonance, Biomolecular; molekulární modely; adenosinmonofosfát; nukleární magnetická rezonance biomolekulární; Oxidation-Reduction; Adenosine Monophosphate; adeninnukleotidy; Adenine Nucleotides; oligoribonukleotidy